A case of nephrogenic syndrome of inappropriate antidiuresis caused by carbamazepine - Sekiya, Naoko (CEN Case Rep, 2017)
We report a case of nephrogenic syndrome of inappropriate antidiuresis caused by carbamazepine (CBZ). CBZ, an antiepileptic drug, is known to cause hyponatremia. The mechanism is generally considered to be inappropriate secretion of antidiuretic hormone, whereas an experimental study suggests a direct effect of CBZ on the kidney by stimulating vasopressin receptor. An 18-year-old male with atypical autism and epilepsy has been treated with CBZ and clobazam since age 9 and 10 years, respectively. At age 11, he was found to have asymptomatic hyponatremia. He had the habit of drinking tea approximately 3 L/day. The low plasma osmolality and high urine osmolality and sodium concentration in the presence of normal thyroid and adrenal function were compatible with syndrome of inappropriate excretion of antidiuretic hormone. His plasma vasopressin level, however, was undetectable. Urine cyclic AMP level was higher than expected from urine osmolality despite the suppressed plasma arginine vasopressin. With fluid restriction, hyponatremia improved. CBZ tapering begun later in the course maintained normal serum sodium concentrations with less strict water intake. This case demonstrates the direct effect of CBZ stimulating vasopressin receptor in the kidney leading to nephrogenic syndrome of inappropriate diuresis.